The Fuss about Artificial Intelligence in Education Sector: Should we Worry? - Chembe, Christopher; Nasilele, Nasilele Brian; Msendo, Robert (Zambia ICT Journal, 2023)
Artificial intelligence (AI) is rapidly changing the world, and education is no exception. AI-powered technologies are being used to automate tasks, personalize learning, and create new educational experiences. This has led to a great deal of excitement about the potential of AI to transform education. However, there are also concerns about the ethical implications of AI in education. In this paper, we explore the potential benefits and risks of AI in education. We argue that AI has the potential to improve education in many ways, but that it is important to carefully consider the potential challenges before widespread adoption. By carefully planning for the future of AI in education, we can ensure that it is used to improve education for all students. The findings from this study contribute to the ongoing discussion on the role of AI in higher education institutions in the changing economic environment and provide insights into the effective integration of AI to enhance educational quality, relevance, and employability outcomes.